The Evidentiary Strength of Land Title Certificates in Civil Cases: A Study of Decisions of the Makassar District Court - Syah, A. Nurul Annisa Dela Putri; Nawi, Syahruddin; Poernomo, Sri Lestari (SIGn Jurnal Hukum, 2025)
Land title certificates are normatively designed as the strongest evidentiary tool; however, their validity is frequently annulled by court decisions due to the negative publication system, which is at odds with the positive trend in national agrarian law. This research aims to analyze the dualism in the legal construction of evidentiary strength, evaluate its relativity in dispute practice at the Makassar District Court, and examine the juridical implications of Article 64 of Government Regulation Number 18 of 2021 on legal certainty. The research method applies an empirical juridical type, combining dogmatic analysis of legislation with a study of field facts through interviews with judges and a review of court decisions. The research results reveal a dogmatic conflict between the certificate as an authentic deed with “perfect” value under the Civil Code and the “strong” predicate under Law Number 5 of 1960. Empirical findings at the Makassar District Court confirm that the certificate’s strength is relative, where the five-year rechtsverwerking protection fortress is consistently set aside by judges if bad faith or substantial legal defects are proven. Furthermore, the implementation of Government Regulation Number 18 of 2021 introduces a new paradigm: “administrative amnesty” after five years, while maintaining avenues for judicial correction in civil disputes. This study concludes that the legal certainty of current certificates is dichotomous: administratively absolute yet judicially open, thereby recommending layered due diligence in every rights transfer to guarantee material validity.